New Method to find initial basic feasible solution of Transportation Problem using MSDM - Morade, N M (International Journal of Computer Sciences and Engineering, 2025)
The optimization processes in mathematics, computer science and economics are solved effectively by choosing the best element from set of available alternatives elements. The most important and successful applications in the optimization refer to transportation problem, that is a special class of the linear programming in the operation research . The main objective of transportation problem solution methods is to minimize the cost or the time of transportation. Most of the currently used methods for solving transportation problems are trying to reach the optimal solution, whereby, most of these methods are considered complex and very expansive in term of the execution time. Finding an initial basic feasible solution is the prime requirement to obtain an optimal solution for the transportation problems. In this paper, a new method named minimum supply & demand method is proposed to find an initial basic feasible solution for the transportation problems. The method is also illustrated with numerical examples.